UNDERSTANDING GUT HEALTH IN CHILDREN WITH AUTISM: NEW PERSPECTIVES AND THERAPEUTIC STRATEGIES - Joanna Kośka; Gabriela Łocik; Katarzyna Moliszewska; Paweł Kukiełka; Julia Mazurek; Julia Załęcka; Alicja Nowik; Kacper Dywan; Martyna Musiorska; Michał Błaszkiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Autism Spectrum Disorder (ASD) encompasses a range of neurodevelopmental traits that influence perception, communication, and social interaction, often accompanied by restricted behaviors and sensory sensitivities. This overview examines the relationship between ASD and gastrointestinal (GI) issues, which frequently co-occur and significantly impact quality of life for affected individuals. Gastrointestinal problems including constipation, diarrhea, and food sensitivities are commonly observed in children with ASD. These issues likely result from multiple interacting factors such as microbiota dysbiosis, immune dysregulation, intestinal hyperpermeability, and dietary patterns. Research has identified disrupted gut microbiome profiles in children with ASD, with increased presence of pathogenic bacteria and associated immune reactivity, including anti-gliadin antibodies. Diagnosing GI disorders in individuals with ASD remains challenging due to communication barriers and atypical sensory processing, with no standardized diagnostic methods currently available. Treatment approaches focus on microbiota restoration through dietary modifications, probiotics, and emerging therapies like Microbiota Transplant Therapy (MTT). Recent studies of MTT have demonstrated sustained improvements in both GI and behavioral symptoms, suggesting promising directions for future interventions that address both the gastrointestinal and behavioral aspects of ASD. Further research is needed to develop standardized diagnostic protocols and evidence-based treatments for this population.